On the objectives and results of the Handel T. Martin paleontological expedition (1903-04) to the Santa Cruz Formation in southern Patagonia - Vizcaíno, Sergio Fabián (2016)
Between January and June 1904, Handel T. Martin (1862-1931), of the University of Kansas (KU), collected fossil vertebrates from the Early Miocene Santa Cruz Formation along the Río Gallegos and the Atlantic Coast of Patagonia, as his own private initiative. In his account of the expedition, Martin stated that when he and his companion, arrived in Buenos Aires, they visited Florentino Ameghino at the Museo Nacional. Martin’s album of photographs shows that he also visited the Museo de La Plata and Ameghino’s home in La Plata. Before heading to Patagonia, Martin assembled his equipment in Bahía Blanca, where his brother had settled. It is not clear if Martin collected a total of 235 or 395 specimens. Clearly, his main goal was to collect fossils to sell, as many specimens were later sold to different institutions in the United States and Europe by Martin himself and through Robert Ferris Damon, a well-known fossil and mineral trader of the time. To date, we have identified only about 170 specimens in formal collections. A large part of the collection – at least 130 of the choicest specimens – remained at KU, which constitutes one of the largest collections of Santacrucian vertebrates outside Argentina (in addition to the ones in the Yale Peabody Museum in New Haven, the Field Museum in Chicago, and the American Museum in New York). Although the collection at KU is largely neglected by paleontologists and has seldom been studied, it contains a good representation of the Santacrucian fauna, with many fine specimens.